REEVALUATING PREVIOUS CONCEPTS OF â€œTHE NATIONâ€ - TakÃ¡cs, Izolda (European Scientific Journal, ESJ, 2015)
In my hypothesis the concept of the nation is present, and it could be defined precisely in SzÃ©chenyiâ€™s work. The aim of my paper is to prove, or to cast way this hypothesis. My statement will be supported by quotes from SzÃ©chenyi. In my opinion our image and concept of the Hungarian nation has been made up by nation concepts like these. They come to the forefront more and more. Namely, the analysis of the nation concept of the â€œgreatest Hungarianâ€ could make us more aware of the genealogy of our Hungarian national consciousness.